Active Control of a Small-Scale Wind Turbine Blade Containing Magnetorheological Fluid - Fevzi Cakmak Bolat; Selim Sivrioglu (Micromachines, 2018)
This research study proposes a new active control structure to suppress vibrations of a small-scale wind turbine blade filled with magnetorheological (MR) fluid and actuated by an electromagnet. The aluminum blade structure is manufactured using the SH3055 (Bergey Windpower Co. Inc., Norman, OK, USA) code numbered airfoil which is designed for use on small wind turbines. A dynamic interaction model between the MR fluid and the electromagnetic actuator is constructed to obtain a force relation. A detailed characterization study is presented for the proposed actuator to understand the nonlinear behavior of the electromagnetic force. A norm based multi-objective H2/H∞ controller is designed using the model of the elastic blade element. The H2/H∞ controller is experimentally implemented under the impact and steady state aerodynamic load conditions. The results of experiments show that the MR fluid- electromagnetic actuator is effective for suppressing vibrations of the blade structure.